Doppler Velocimetry of Umbilical Artery in Normal and Growth Restricted Pregnancy (Bangladesh Journal of Obstetrics & Gynaecology, 2022)
Objectives: To evaluate the umbilical arterial blood flow velocity and its various indices during 3rd trimester of pregnancy and to compare these indices in normal and growth restricted pregnancies.Methods: In this study, 50 women with normal singleton pregnancy and 50 women with intrauterine growth restricted (IUGR) pregnancy with expected birth weight